Experimental Investigation of Bond Stress and Deformations in LWAC Ties Reinforced with GFRP Bars. (9th May 2014) - Carmo, R. N. F.; Costa, H.; Bento, G.
ABSTRACT The structures' durability is an engineering concern for a long time but has been increased in the last years. Lightweight aggregate concrete (LWAC) combined with glass fibre reinforced polymer bars allows to create structures with high performance in terms of durability. The glass fibre reinforced polymer (GFRP) bars have different ribs from those of steel bars, and consequently, its bond to concrete is affected. Moreover, the Young's modulus of GFRP is much below compared with that of steel, and this influences significantly the behaviour of structural elements reinforced with this material. This paper presents an experimental study focused on bond between LWAC and reinforcing bars of GFRP. Thirty‐six pull‐out tests were carried out using steel and GFRP bars. These reinforcements were combined with three types of concrete, all with the same design density 1900 kg m−3 but with different values of compressive strength: 35, 55 and 70 MPa. Furthermore, 12 reinforced ties were tested, combining different types of bars (steel and GFRP), two different diameters (12 and 16 mm) and the three types of LWAC. Based on experimental results, several relations were established to understand the behaviour of LWAC structures reinforced with GFRP bars, mainly in the serviceability conditions. These results point out that ties deformation and crack width are very affected by the reduced Young's modulus of GFRP: deformations and crack width of ties reinforced with GFRP are significantly higher, approximately three times greater, compared with those of ties reinforced with steel. The tension stiffening effect was also analysed in detail, and it was found that it is slightly influenced by the concrete compressive strength but is highly dependent of the Young's modulus of the reinforcing material.